The effectiveness of lamtoro(Leucaena sp.) leaf extract on the growth of weed in young tea - Sobar Darana (Jurnal Penelitian Teh dan Kina, 2011)
A research to determine the effectiveness of lamtoro leaf extract on the growth of weeds in young tea plantation was carried out in Pasir Sarongge Experimental Garden and Plant Protection Laboratory RITC Gambung from June to December 2009. Researches on the effectiveness of lamtoro leaf extracts on the germination of weed’s seed, and on the growth of weeds in the field, were conducted. Lamtoro leaf extract treatment at various concentrations tried, suppressed the germination of seeds of broadleaf weeds (hareuga and babadotan) in the laboratory. In general, the germination suppression were increases with increasing the concentration of the extracts tested. Spraying of lamtoro leaf extract (Leucaena sp.) starting at concentration of 7.50% resulted better control effect and significantly different compared to controls. In addition, spraying treatment of lamtoro leaf extract could reduce the number of weed species.